Timing of crystallization of the lunar magma ocean constrained by the oldest zircon - Nemchin, Alexander; Timms, Nicholas Eric; Pidgeon, Robert; Geisler, T.; Reddy, Steven; Meyer, C (Nature Publishing Group, Macmillan Publishers Ltd, 2009)
The Moon is thought to have formed through the consolidationof debris from the collision of a Mars-sized body with the Earthmore than 4,500 million years ago. The primitive Moon wascovered with a thick layer of melt known as the lunar magmaocean1, the crystallization of which resulted in the Moon?ssurface as it is observed today. There is considerable debate,however, over the precise timing and duration of the processof magma ocean crystallization. Here we date a zircon fromlunar breccias to an age of 4,4176 million years. This dateprovides a precise younger age limit for the solidification ofthe lunar magma ocean. We propose a model that suggestsan exponential rate of lunar crystallization, based on acombination of this oldest known lunar zircon and the age of theMoon-forming giant impact. We conclude that the formationof the Moon?s anorthositic crust followed the solidification of80?85% of the original melt, within about 100 million years ofthe collision. The existence of younger zircons2 is indicative ofthe continued solidification of a small percentage of melt for anextra 200?400 million years.